Evaluation of wind shear coefficient and surface roughness for selected cities in southwestern Libya (Sebha University Conference Proceedings, 2025)
This paper aims to evaluate the wind shear coefficient for six selected sites in southwestern Libya, namely (Ghat, Murzuq, Qatrun, Sebha, Ubari and Trahgan (. Wind speeds from )1981 to 2022(at 10 m and 50 m above the ground surface were applied, which were obtained from NASA database were applied. The wind shear coefficient and surface roughness were calculated and the results were tabulated and curves presented too for each site by using the power law. By obtaining the wind shear coefficient and surface roughness, it became possible to use extrapolation of the wind speeds at the desired turbine hub height for any of the selected sites.